REINTEGRASI HUKUM KOMPREHENSIF DALAM PENCEGAHAN KEJAHATAN TEKNOLOGI DI ERA REVOLUSI INFORMASI - Danny Trisno Susetyo; Aditya Fajri Kurnia Pradana (Tahta Media Group, 2024)
New regulatory efforts and adjustments to various regulations in the Information Technology sector, aim to analyse the factual events shown and determine the legal issues or issues raised by these factual events, so that changes can be made to the Law in various sectors that use the basis of information technology or internet-based systems, in order to harmonise the various arrangements contained in various laws into 1 (one) law comprehensively, in connection with the influence of the rapid development of information technology, which inevitably, ready or not ready, we must face. In this paper, the author uses a normative legal research method, by analysing materials and data in a descriptive qualitative manner, which provides an explanation of subjective analysis by making observations in Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Information and Electronic Transactions, whether it covers the risk of criminal acts against the use of human robots and the use of autonomous cars without a driver who can fly. It is inevitable that the rapid changes in internet-based technology require anticipatory steps in shaping the rule of law. The author concludes that in the era of the information technology revolution, technological transformation in various industrial sectors, which can lead to cybercrime, must be quickly anticipated with clear legal rules.